Maximizing Network Throughput in Heterogeneous UAV Networks - Li, Shuyue; Li, Jing; Xiang, Chaocan; Xu, Wenzheng; Peng, Jian; Wang, Ziming; Liang, Weifa; Yao, Xinwei; Jia, Xiaohua; Das, Sajal K (IEEE/ACM transactions on networking, 2024)
In this paper we study the deployment of an Unmanned Aerial Vehicle (UAV) network that consists of multiple UAVs to provide emergent communication service for people who are trapped in a disaster area, where each UAV is equipped with a base station that has limited computing capacity and power supply, and thus can only serve a limited number of people. Unlike most existing studies that focused on homogeneous UAVs, we consider the deployment of heterogeneous UAVs where different UAVs have different computing capacities. We study a problem of deploying K heterogeneous UAVs in the air to form a temporarily connected UAV network such that the network throughput- the number of users served by the UAVs, is maximized, subject to the constraint that the number of people served by each UAV is no greater than its service capacity. We then propose a novel O\left({\sqrt {\frac {s}{K}}}\right) -approximation algorithm for the problem, where s is a given positive integer with 1 \le s\le K , e.g., s=3 . We also devise an improved heuristic, based on the approximation algorithm. We finally evaluate the performance of the proposed algorithms. Experimental results show that the numbers of users served by UAVs in the solutions delivered by the proposed algorithms are increased by 25% than state-of-the-arts.